Histopathologic spectrum of hypersensitivity reactions associated with anti‐CD52 therapy (alemtuzumab). (9th September 2016) - Clark, Stacie L.; Tse, Julie Y.; Fisher, David C.; LeBeouf, Nicole R.; Murphy, George F.; Kupper, Thomas S.; Clark, Rachael A.; Lian, Christine G.
Abstract : Background: Alemtuzumab is a humanized monoclonal antibody directed against CD52, a cell surface antigen on B and T lymphocytes, and used to treat B‐cell chronic lymphocytic leukemia and cutaneous T‐cell lymphoma. Skin rash is a common adverse reaction following treatment with alemtuzumab. However, the clinicopathologic features and immunologic basis for the reaction have not been previously reported. Methods: Our hospital's electronic pathology database was searched for cases with documentation of 'alemtuzumab' or 'anti‐CD52' in the clinical history provided by either the ordering physician or the pathologist. Clinical and histopathologic review of the cases was performed. Results: Five patients with cutaneous T‐cell lymphoma (CTCL) or chronic lymphocytic leukemia (CLL) were treated with alemtuzumab, and developed pruritic, erythematous papules and plaques. Histopathology of the skin lesions revealed subacute spongiotic dermatitis with multifocal parakeratosis, endothelial activation and perivascular lymphocytic infiltrate. Eosinophils were not a prominent feature. Conclusions: We describe the clinicopathologic features of a novel hypersensitivity reaction to alemtuzumb, and hypothesize it may be due to an immunologic response precipitated by the persistence of resident memory T‐cells (TRM ) in the skin. Our findings raise awareness for a novel reaction pattern and guide the histopathologic interpretation of lesions which may clinically mimic residual or recurrent cutaneous lymphoproliferative disorders.